The agnostic age law, religion, and the Constitution - Horwitz, Paul. (New York ; Oxford : Oxford University Press, 2011)
The Agnostic Age: Law, Religion, and the Constitution is a book for lawyers, law professors, law students, lawmakers, and any citizen who cares about church-state conflict and about the relationship between religion and liberal democracy.
Specialized.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Freedom of religion -- United States; Religion and law -- United States; Agnosticism -- United States; Liberalism (Religion) -- United States; Law